Diffusing the Ubuntu philosophy into e-Government: A South African Perspective - (:unkn) unknown (My University, 2010)
Information Systems (IS) researchers are increasingly calling for contextual approaches to Information and Communication Technologies (ICT) innovations [1]. The call proceeds from the realization that ICT and e-government policies are often adopted and developed with a blind focus on the ICT artifact, and with little reflection on the contribution of ICT to the context [2]. This paper emanates from an ethnographic study that investigated how ICT can facilitate government policy implementation in a development context. The study found it necessary to understand the role of tradition and its potential influence on ICT implementations in South Africa. The paper reviews the context of the South African government and its conspicuous inclination to the way of life, Ubuntu. Ubuntu is growing in popularity and is increasingly being applied as an African solution to African problems such as poverty, political strife and trade. Using Grounded Theory analysis, the findings revealed the critical importance of ICT not threatening tradition but rather complementing it, the role that ICT could play in enabling or enhancing community assemblies, and the marginalized role of women citing how ICT might be used as a means to empower rather than marginalize women even further. We conclude that e-government needs to be re-conceptualized in South Africa for a more culturally acceptable and relevant approach to the use of ICT innovations for development.
Keywords: African Research